Cloud Computing in U.S. Healthcare: Advancing Patient Care through Digital Transformation - Viswaprakash Yammanur (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article analyzes the transformative impact of cloud computing technology on the United States healthcare system, highlighting its role in advancing patient care through digital transformation. The article examines key aspects, including cloud infrastructure, data management and analytics, operational efficiency through automation, and telehealth delivery systems. It addresses how cloud-based solutions revolutionize healthcare delivery by enabling seamless data sharing, enhancing security protocols, and improving operational efficiency. The article shows the integration of emerging technologies such as blockchain, artificial intelligence, and the Internet of Things (IoT) in healthcare applications, demonstrating their collective contribution to improved patient outcomes. The article also explores how these technological advancements are particularly beneficial in addressing healthcare accessibility challenges in rural and underserved communities. Through detailed analysis of implementation strategies and future trends, this article provides valuable insights into the essential role of cloud computing in modernizing healthcare delivery systems while ensuring security, compliance, and optimal resource utilization.